Volksgemeinschaft am Ende. Gesellschaft und Gewalt 1944/45 - Keller, Sven (Quellen und Darstellungen zur Zeitgeschichte, 2013)
The ubiquitous violence of the Nazi regime reached its climax just as it was collapsing. Systematic terror served to stabilize the regime and preserved its ability to act until the very end. This terrible epilogue to Hitler`s rule is described in striking detail, drawing on an extremely broad range of sources.